Methods of Assessing the Labor Progress: A Review Study - Morvarid Irani; Masoumeh Kordi; Marzieh Lotfalizadeh (Mashhad University of Medical Sciences, 2019)
Introduction: Assessing the labor progress is one of the primary and important cares during childbirth. The methods used to evaluate the progress of labor should have the least damage to the mother and the fetus. This review study was performed with aim to assess the methods of labor progress. Methods: In this review study, the Persian and English articles which were published during 1997 to 2018 and were indexed in databases of PubMed, Magiran, Google Scholar, Iranmedex, Irandoc and SID with keywords of progress of labour, vaginal examinations, cervical dilatation, and purple line were searched. The articles which had inclusion criteria entered to the study and were qualitatively analyzed.  Results: A total of 43 studies which were extracted from 385 articles related to the assessing the progresses of labor were studied. The results of articles performed in this field were divided in three general categories including: determination of cervical dilation by vaginal examination, methods which consisted of several indicators such as maternal behavioral and physiologic changes, and discoloration of the skin between the buttocks (purple line). Conclusion: Vaginal examination is not the only method to evaluate the progress of labor and midwifes can use a set of signs and symptoms including observation of the purple line and measuring it, assessing the changes in the number of respiration, behaviors, voices, movements and positions of the mother during labor in order to reduce the number of vaginal examinations and therefore improve the mother and fetus healthy in clinical practice.